2012
DOI: 10.1002/app.38834
|View full text |Cite|
|
Sign up to set email alerts
|

Development of olive oil based organogels using sorbitan monopalmitate and sorbitan monostearate: A comparative study

Abstract: The present work deals with preparation of the olive oil (OO) based organogels using sorbitan monostearate (SMS) and sorbitan monopalmitate (SMP) as organogelators for controlled drug delivery applications. Metronidazole (MZ) was used as the model drug. Gels were prepared by solubilizing the organogelators in OO at 60°C under stirring. As the solution was cooled down, the gelator molecules precipitate as an isotropic phase having networked structures, which immobilized OO. Formation of 3D networked structure w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
8

Relationship

8
0

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 42 publications
1
43
0
Order By: Relevance
“…In general, water-devoid organogels require a high gelator concentration to induce gelation. Shah et al found the minimum sorbitan monostearate concentration to be 20% w/w using olive oil as apolar phase (13). Behera et al used 18% w/w of sorbitan monostearate for preparing sunflower oil-based organogels (37).…”
Section: Preparation Of the Organogelsmentioning
confidence: 98%
See 1 more Smart Citation
“…In general, water-devoid organogels require a high gelator concentration to induce gelation. Shah et al found the minimum sorbitan monostearate concentration to be 20% w/w using olive oil as apolar phase (13). Behera et al used 18% w/w of sorbitan monostearate for preparing sunflower oil-based organogels (37).…”
Section: Preparation Of the Organogelsmentioning
confidence: 98%
“…Sorbitan monostearatebased organogels have also been developed for pharmaceutical applications (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…FWHM has been reported to be inversely related to the crystallinity of the formulations. [32] The results suggested that the incorporation of MC into the pHEMA matrix resulted in the increased crystallinity of the HM2. A further increase in the MC Table 2.…”
Section: Xrd Studiesmentioning
confidence: 96%
“…The organogels were prepared by heat-cool method as per the reported literature [15]. In short, accurately weighed stearic acid and vegetable oil mixture was heated in a water-bath maintained at 70 ºC for 15 min to form a clear homogenous solution.…”
Section: Preparation Of Organogelsmentioning
confidence: 99%
“…Hemocompatibility of the microparticles was evaluated using goat blood as per the ASTM standard protocol described earlier [15,26]. The cytocompatibility of the microparticles was determined against MG63 osteoblast cells.…”
Section: Biocompatibility and Mucoadhesivity Studiesmentioning
confidence: 99%